Smart parking system - Gawande, Shubhangi; Kamle, Shital (International Journal of Computer Sciences and Engineering, 2025)
Parking issue is a big challenge to facilitate traffic network and ensure city life quality. Searching for parking space in most city area especially during the rush hour is difficult. For device the difficulty arises from not knowing where the parking space is available. This paper presents a review of various techniques which are already implemented to solve the parking issue. This paper also presents a mechanism to solve the issues. The aim of this project is to provide a user friendly reliable parking system application. The common method of finding parking space is manual where the driver usually find space in street through luck and experience this process take time and efforts and may lead to the worst case of failing to find parking space for the driver if driver is driving in the city with high vehicle density. Smart parking system typically obtains information about availability of parking space in nearby area and process real time data to place vehicle at available position. Smart parking system uses mobile application for automated mobile payments. Smart parking system is useful to solve the issue of parking traffic congestion.